Assessing Continuing Education Needs in Alveolar Dental Traumatology for Dental Interns - El kharroubi, Soukaina; Amarir, Hind; Doumari, Bouchra; Karami, Malika (Journal of University College of Medicine and Dentistry, 2024)
Objective: In the Emergency Department of the dental consultation and treatment center of the university hospital IBN ROCHD in Casablanca, the management of oral trauma is mainly carried out by dental interns. In view of the difficulties observed and reported by them concerning certain traumas, it seemed necessary to set up a training course in traumatology to optimize the management of patients consulting the emergency department. The objective of this study was to draw up a preliminary analysis of the dental trauma training needs of interns working at our university hospital. Methodology: Two methods were utilized, individual interviews and a questionnaire, to gather information about training needs. The responses were then prioritized using the FGP (Frequency, Severity, Problem) grid. Results: Following the initial meeting with dental interns, three key areas were identified: root fractures, complete dental dislocation, and alveolar fractures. Responses were collected from all 29 interns, who expressed a requirement for acquiring knowledge, expertise, and interpersonal skills regarding these three areas. For Knowledge Problems, interns indicated a necessity for theoretical understanding in handling alveolar fractures (1.45±1.183), with root fractures scoring lower (1.03±1.017), and total dislocation being the lowest priority (0.34±0.769). In terms of knowhow problems, alveolar fractures had the highest score (2.34±1.317), followed by root fractures (1.72±1.032), and total dislocation ranked last with an average of (1.03±1.149). Regarding interpersonal skills problems, practitioners mainly experienced problems related to total tooth dislocation (1.17±1.365), followed by alveolar fractures (1.03±1.375), and lastly, root fractures (0.97±1.267). Conclusion: The present study demonstrated a clear requirement for ongoing education in alveolo-dental traumatology among the interns at university hospital.